2016
DOI: 10.1007/s00216-016-9513-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA enrichment approaches to identify unauthorized genetically modified organisms (GMOs)

Abstract: With the increased global production of different genetically modified (GM) plant varieties, chances increase that unauthorized GM organisms (UGMOs) may enter the food chain. At the same time, the detection of UGMOs is a challenging task because of the limited sequence information that will generally be available. PCR-based methods are available to detect and quantify known UGMOs in specific cases. If this approach is not feasible, DNA enrichment of the unknown adjacent sequences of known GMO elements is one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…are currently discussed (Akogwu, Wang, Zhang, & Gong, 2016). On the other hand, NGS may be applied to rapidly generate sequence data in order to identify unknown genomic insertions/deletions and genetic modifications with potential application as basis for developing specific detection methods (Arulandhu et al, 2016, Barbau-Piednoir, De Keersmaecker, Delvoye, et al, 2015). The present work is based on the use of two second generation sequencing technologies (Illumina and 454).…”
Section: Discussionmentioning
confidence: 99%
“…are currently discussed (Akogwu, Wang, Zhang, & Gong, 2016). On the other hand, NGS may be applied to rapidly generate sequence data in order to identify unknown genomic insertions/deletions and genetic modifications with potential application as basis for developing specific detection methods (Arulandhu et al, 2016, Barbau-Piednoir, De Keersmaecker, Delvoye, et al, 2015). The present work is based on the use of two second generation sequencing technologies (Illumina and 454).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional qPCR applications (SIMQUANT; Berdal et al 2008) use qPCR chemistry together with the limiting dilutions principle, which is near to the idea of the ddPCR-based methods, of which two were included Dobnik et al 2015). Other selected methods include LAMP with end-point fluorescent (Chen et al 2011;Wang et al 2015) or bioluminescence real-time detection (Kiddle et al 2012), multiplex PCR with hybridization on microarrays (Leimanis et al 2008;Hamels et al 2009) or detection with capillary gel electrophoresis (Nadal et al 2006), a protein-based method (Van Den Bulcke et al 2007), and two NGS methods (unpublished, developed within the EU FP7 Decathlon project), one for enriched samples and another for whole genome sequencing (see, e.g., Arulandhu et al 2016;Holst-Jensen et al 2016). The majority of the selected methods are validated in-house or within international collaborative trials and their fitness for purpose demonstrated elsewhere (see Table 1 for references).…”
Section: Analytical Methods Assessed In This Studymentioning
confidence: 99%
“…Whole-genome sequencing was shown to be applicable for detection and characterization of GMOs and derived products; however, there are still problems with sensitivity for all targets [33]. To increase sensitivity, DNA enrichment approaches can be coupled with NGS [34], and such a combination can allow reliable identification of authorized and unauthorized GMOs [35]. The main drawback of NGS is currently the price and complex data analysis, which restricts its routine use.…”
Section: Overview Of Different Technologies Used For Gmo Detectionmentioning
confidence: 99%